2007
DOI: 10.1017/s1751731107000663
|View full text |Cite
|
Sign up to set email alerts
|

Carryover of aflatoxin from feed to milk in dairy cows with low or high somatic cell counts

Abstract: Aflatoxin M1 (AFM1) residues in milk are regulated in many parts of the world and can cost dairy farmers significantly due to lost milk sales. Additionally, due to the carcinogenicity of this compound contaminated milk can be a major public health concern. Thirty-four lactating dairy cows were utilised to investigate the relationship between somatic cell counts (SCC), milk yield and conversion of dietary aflatoxin B1 (AFB1) into milk AFM1 (carryover (CO)). The AFM1 in milk increased as soon as the first milkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
124
2
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(150 citation statements)
references
References 19 publications
15
124
2
7
Order By: Relevance
“…AFB 1 quickly appears in cows (as AFM 1 metabolite in blood after just 15 min (Moschini et al, 2006) and in milk at the first milking (Diaz et al, 2004;Masoero et al, 2007) after ingestion of aflatoxin-contaminated feed. We recently demonstrated that, in Beja province (Tunisia), milk and milk by-products were contaminated with high levels of AFM 1 (3-4-fold above the permitted dose) (Abbès et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…AFB 1 quickly appears in cows (as AFM 1 metabolite in blood after just 15 min (Moschini et al, 2006) and in milk at the first milking (Diaz et al, 2004;Masoero et al, 2007) after ingestion of aflatoxin-contaminated feed. We recently demonstrated that, in Beja province (Tunisia), milk and milk by-products were contaminated with high levels of AFM 1 (3-4-fold above the permitted dose) (Abbès et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The Aspergillus mycotoxin aflatoxin B 1 (AFB 1 ) is of great interest for the dairy farmer because it contaminates feeds, which are commonly fed to lactating cows (Sweeney and Dobson, 1998). The AFB 1 is metabolized by the cow and excreted as its derivative aflatoxin M 1 (AFM 1 ) into the milk (Masoero et al, 2007). The EU regulation is extremely severe about the contamination with aflatoxins in the diets of lactating cattle, with a threshold of 0.005 ppm; instead, diets for growing cattle can contain up to 0.020 ppm (European Commission, 2003).…”
mentioning
confidence: 99%
“…In a metaanalysis of transition rates, Pettersson (29) found that the CO rate of AFB1 to milk was between 0.18- that milk yield is the major factor affecting the AFM1 excretion. Thus, higher milk yield results in higher AFM1 excretion (8,14,15 A seasonal effect of aflatoxin M1 concentration has been reported in some studies, in which it was observed a higher concentration of AFM1 in cold seasons than in hot seasons because farmers tend to use higher amounts of compound feeds in winter (34). In other words, animals consume less concentrated feeds in summer because they also graze on pasture.…”
Section: Discussionmentioning
confidence: 94%
“…In order to protect the consumer from the harmful effects of aflatoxin, the maximum level of AFM1 in milk and milk products is restricted by many governments, as is the level of AFB1 in feedstuffs (7). The defined maximum limit is 0.5 µg/kg in the USA and 0.05 µg/kg in the European Union, Africa, Asia and Latin America (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation